Effects of N Fertilization During Cultivation and Lactobacillus plantarum Inoculation at Ensiling on Chemical Composition and Bacterial Community of Mulberry Silage - Li, Ping; You, Minghong; Du, Zhouhe; Lu, Yongxiang; Zuo, Chunyan; Zhao, Man; Wang, Honglin; Yan, Xu; Chen, Chao (Frontiers in Microbiology, 2021)
As unconventional forage source, mulberry (Morus alba L.) has been cultivated to alleviate animal feed shortages. This study aimed to investigate the effects of N fertilization during cultivation and Lactobacillus plantarum inoculation at ensiling on the chemical composition and bacterial community of mulberry silage. Mulberry was separately cultivated under two N fertilization rates (N1, 390 kg/ha/year; N2, 485 kg/ha/year) in 2016-2019, harvested on 30 April（the first-cut）and 15 June ( the second-cut) in 2019, and then chopped for producing small bag silage. The silage was treated without (control) or with L. plantarum (LP, a recommended application rate of 105 cfu/g on fresh matter basis). After storage of 60 days in dark room at ambient temperature, silage was sampled for analysis of chemical and microbial compositions. Higher (P<0.05) final pH value and acetic acid content and lower (P<0.05) lactic acid content were found in silage under N2 fertilization, resulting in more dry matter loss than in silage under N1 fertilization. Compared with control, inoculation of LP at ensiling increased (P<0.05) lactic acid content and decreased (P<0.05) final pH value, acetic acid and propionic acid contents of silage, by advancing the dominance of Lactobacillus and reducing the abundance of Enterococcus and Enterobacter. In addition, inoculation of LP at ensiling decreased (P<0.05) dry matter loss and butyric acid content of first-cut silage. In conclusion, inoculation of LP at ensiling could reduce the undesirable effects from high N fertilization rate during cultivation on silage quality of mulberry harvested at different growing seasons.